Implementing a Transparent and Sustainable E-resource Assessment Plan in an Era of Continual Change - Ralph, Taylor (Library resources & technical services, 2024)
Most academic libraries perform some level of collection assessment for e-resources. However, traditional e-resource assessment procedures pose multiple challenges related to their adaptability, transparency, and sustainability. At the Valley Library at Oregon State University, a multi-tiered assessment process is continually revised and refined to reflect the changing scholarly communication landscape and address the needs of both our library and our community. This paper discusses how this collection assessment system is currently set up, and outlines the challenges, benefits, and future considerations for other libraries interested in adapting their own e-resource assessment practices.